Sistema de información cliente/servidor para la cooperativa de transportes copuigua del cantón Pujilí - Casa Tigsilema, Diego Fernando (2016)
An evaluation about the actual situation of ―COPUIGUA‖ Cooperative Transportation was made respecting the information management. This cooperative is located in Guápulo Pujilí Canton. The observation and interview techniques were used for data information. Through that, it was identified that there wasn’t an automatized method storage and Data Recovery. Which causes a poor management of the information which is daily produced in this Cooperative. It affects to the customer’s quality service and therefore the cooperative operation. As a result, a system was development in order to expedite the organization and information update. The development system was based on the Kanban Methodology which helped fundamentally in the development information system process. So, a contribution to the computer application was achieved which provides the Automation of Registration and information research process. In addition, this system is friendly with the environment, because the waste of natural resources such as paper was avoided.